Effect of irrigation with brackish water in rice (Oryza sativa) wheat (Triticum aestivum ) cropping system - SINGH, V; AGARWAL, S K (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during winter seasons of 1987-88 to rainy season of 1990 to ovaluate the effect of irrigatio with brackish water in rice (Oryza sativa L.)-wheat (Triticum aestivum L, emend, Fiori & Paol) cropping sequence at Kanpur, Both the crops wore irrigated with tube-well water which Was slightly brackish, and contained a considerable quantity of sodium bicarbonate (Na+ 8.3 meq/litre and HCO3-19.5 meq/litre), Soil amendments such as gypsum @ 750 kg/ha or pyrite @ 600 kg/ha alone or in combination with farmyard manure @ 2 tonnes/ha were applied in 8 treatments combinations before transplanting rice and sowing wheat Randomized block design was followed with 3 replications, Maximum yields of rice (4,97 tonnes/ha and wheat (4.70 tonnes/ha) were recorded with soil application of 500 kg/ha pyrite + 2 tonnes/ha farmyard manure, followed by rice(Â 4,747 tonnes/ha) and wheat (4.483 tonnes/ha) on application of 750 kg/ha gypsum + 2 tonnes/ha farmyard manure, which were significantly higher than the control (no amendment). The grain yield increased by 21 and 23% in rice and wheat respectively when compared with the control. This treatment gavo Rs 4 635/ha higher net return than the control and minimized the ill-effect of brackish water on the soil compared with tho control.